Hydatid cyst of biceps brachii associated with peripheral neuropathy. (2015) - Tuna, Serkan; Duymus, Tahir Mutlu; Yanik, Hakan Serhat; Durakbasa, Mehmet Oguz; Mutlu, Serhat; Erdem, Sevki
Highlights: Hydatidosis represents the most significant parasitic disorder in the Mediterranean countries. Localization of the primary cyst hydatid infection in the extremity is rare. Primary musculoskeletal cyst hydatid generally affects the proximal muscle groups. Due to the fact that it leads to a mass formation, hydatid cysts may be mistaken for soft tissue tumors. MR is the golden standard of diagnosis and detection of multilocular polycystic lesions. Cases of concomitant neurologic findings and complaints secondary to peripheral nerve compression are very rare. Abstract: Introduction: Hydatidosis represents the most significant parasitic disorder in the Mediterranean countries and leads to major problems through unfavorable effects on the public health and national economy. Localization of the primary cyst hydatid infection in the extremity is rare and biceps brachii localization is also rarely reported in the literature. Presentation of case: A 43-year-old woman, who presented with the complaints of mass and pain in the left arm and numbness of the hand. Laboratory investigations, X-ray and magnetic resonance (MRI) findings revealed hydatid cyst of the biceps brachi muscle. The mass was totally excised and the diagnosis was confirmed by the macroscopic images of the mass and the pathologic results. After the surgery, the patient had an improvement in the nerve compression findings including numbness of the hand and the upper extremity and pain. Discussion: Localization of a primary cyst hydatid infection in the upper extremity is rare and there are no reports of peripheral neuropathy secondary to mass effect. Even if the pre-surgical electromyelography performed for the nerve conduction study reveals a normal result, the potential for the hydatid cysts to cause nerve compression should be taken into consideration in such patients. Conclusion: Cases of concomitant neurologic findings and complaints secondary to peripheral nerve compression are very rare. The clinical findings should not be ruled out even if the EMG result is negative.